2018
DOI: 10.1590/1678-7757-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical ozonetherapy on gingival wound healing in pigs: histological and immuno-histochemical analysis

Abstract: In this study, the effects of ozonetherapy on secondary wound healing were evaluated histologically and immuno-histochemically. Material and Methods: 8 healthy pigs were used in this study. Six wounds with 10 mm in diameter were created through the punch technique on the palatinal gingiva of each pig. Ozone gas was applied on only 3 wounds (test group) and the remaining 3 were left to natural healing (control group). Biopsy samples were taken from one of the wounds in each group on the third day, from another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
2
10
2
Order By: Relevance
“…It was observed that ozone therapy could be effective in the early stages of repair with increased expression of the vascular endothelial growth factor. 11 Other authors have found improved repair of guinea pig skin wounds after using topical ozonated olive oil. 20 In an experimental study, a reduction in the amount of granulation tissue, lower number of inflammatory cells, and wider deposition of collagen type I were observed in Wistar rats with skin lesions that received 0.1 mL of subcutaneous ozone gas daily for 7 and 14 days.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that ozone therapy could be effective in the early stages of repair with increased expression of the vascular endothelial growth factor. 11 Other authors have found improved repair of guinea pig skin wounds after using topical ozonated olive oil. 20 In an experimental study, a reduction in the amount of granulation tissue, lower number of inflammatory cells, and wider deposition of collagen type I were observed in Wistar rats with skin lesions that received 0.1 mL of subcutaneous ozone gas daily for 7 and 14 days.…”
Section: Discussionmentioning
confidence: 98%
“…5 Ozone therapy has been used and studied in several fields of health care. 6,7 In dentistry, some authors use ozone to assist the treatment of generalized chronic periodontitis, 8,9 in indirect dental pulp capping, 10 in oral wound repair, 11 in prosthesis-related traumatic ulcer pain relief, 12 and as an adjunct in the treatment of periimplantitis 13 and osteonecrosis of the jaws. 3 This report aimed to present two cases of facial trauma, with extensive damage to the gingival tissues, in which ozone was used as supportive therapy to help with tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of ozone therapy lays mainly in three aspects: Immunomodulation 2007), antimicrobial activity (Polydorou et al, 2012;Thanomsub et al, 2002) and the capacity to interplay with the oxidant/antioxidant balance (Soares et al, 2019). Altogether, another main aspect of the mechanism of the ozone treatment is the wound healing property and the main mechanism behind this is the capacity to interact with the skin epithelization system (Borges et al, 2017;Eroglu et al, 2018), as summarized in Fig. 1.…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…As well as increased vessel numbers and collagen deposition (Soares et al, 2019). Several endogenous growth factors, such as vascular Endothelial Growth Factor (VEGF), Transforming Growth Factor-beta (TGF-β), Fibroblast Growth Factor (FGF) and Platelet-Derived Growth Factor (PDGF), play an essential role in early wound healing (Eroglu et al, 2018), so it becomes crucial for the healing process the stimulation of the expression of these growth factors.…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation